Prevalence of Antibodies Against Chicken Infectious Anaemia Virus Among Free-Range Chickens in Northeastern Libya - Gerish E1*, Mansour L2, Gawas A2, Al-Kateb A3, Al-Khallab E1, Skeeb A1, Al-Ghriany O4; Al-Tajoury5 (AlQalam Journal of Medical and Applied Sciences, 2017)
Chicken Infectious Anaemia Virus (CIAV) has expanded much significance as an immunosuppressive and economically notable emerging aetiology of chickens worldwide. CIAV is the causative agent of Chicken Infectious Anaemia (CIA), an emerging infectious disease mainly noticed in young chicks of 2-4 weeks of age, which usually acquire the infection vertically. The disease is characterised by increased mortality, reduced weight gain, anaemia, aplasia of bone marrow, atrophy of thymus and concomitant marked immunosuppression with enhanced susceptibility to other pathogens and diminished vaccine responses leading to severe economic losses. This research was achieved due to the scarceness of recent facts iabout CIAV in Libya, and it is reported in bordering country near to the study area. For this purpose, in the period of between 3rd and 6th of January 2010, a prevalence study was performed on free-range chickens with collection of 96 serum samples from 15 flocks in northeastern area-Libya, and screened for the presence of CIAV antibodies using indirect enzyme-linked Immunosorbent assay (ELISA) kit. Moreover a structured questionnaire was designed for the purpose of this research and administrated to owners to gather information on demographic and management data. The overall prevalence was 71.87%. The prevalence-within-flock ranged from 60% to 100%. There are age variation in the infection distribution was noted in third breeding interval and significantly lower than other three breeding intervals (P < 0.05). The specific antibodies against CIAV in the flocks of Al-Marj suburb were significantly low (P < 0.05) compared to the rest suburbs. The findings of the current study show that CIAV is widespread among village chicken populations in the surveyed area. Hence, further studies are required to evaluate the epidemiological effects and yield losses of infection in commercial chickens, and to assess the expenditure profit of prevention procedures.